Rise of Saﬀronization, Hindu Fundamentalism and its Regional Implications - Abbasi, Zaib Tayyab (Journal of Pakistan Administration, 2020)
The term 'secular' was incorporated in Indian constitution in 1976. Hindu majoritarianism, however, continued to exercise a strong inﬂuence in India since Partition. The formation of BJP in 1980 and communal riots following destruction of Babri mosque further strengthened Hindu fundamentalist elements and their movement, which perceived Muslims as prime enemies. Subsequent violent events led to popularity of the term 'Saﬀron terror' as an allusion to the traditional use of saﬀron colour by Hindu fundamentalist organizations. Over the years, the term Saﬀronization has come to refer to the growing inﬂuence, and perhaps acceptance, of Hindu nationalist mind set and its embodiment through organized and premeditated acts of violence against minorities.
Keywords: Saﬀronization; Hindu Fundamentalism; Regional Implications; BJP; violent events